Epidemiological analysis of Schistosomiasis Mansoni in Brazilian regions (Research, Society and Development, 2022)
Objective: To analyze the reported cases and the prevalence of schistosomiasis in Brazil, from 2007 to 2017. Methodology: This is an ecological study, using the Database of the Disease and Notification Information System (SINAN) and the Brazilian Institute of Geography and Statistics (IBGE). The variables sex, age group, race/color and education per region and year of notification were selected. Furthermore, the prevalence of each variable was calculated, per 100 000 inhabitants, in order to perform the Prais-Winsten regression, Generalized Least Squares and Odds Ratio. Results: In total, 144 755 cases were reported in non-endemic areas of Brazil, from 2007 to 2017. Most records were found in the Southeast (n=96 411) and Northeast (n=45 774) regions; in males (n=87 149); adults aged 20 to 39 years (n=58 347); brown (n=71 843); and incomplete 1st to 4th grade (n=23 060). The trends showed a decline in the analyzed variables, except for the regions of notification and education. As for the odds ratio, the categories female gender, age group from 20 to 39 years old, brown color/race and level of education from the 5th to the 8th grade were identified as vulnerable to the disease. Conclusions: The analyzes showed that the schistosomiasis scenario in Brazil is still a concern, and that improvements are needed in towards public policies and disease control in non-endemic areas.